Effect of Grafting Dates, Methods on Success and Growth of Mandarin (Citrus reticulata Blanco) Sapling - Chalise, B; Baral, DR; Gautam, DM; Thapa, RB (Nepal Journal of Science and Technology, 2013)
A field experiment was conducted at National Citrus Research Program (NCRP), Paripatle, Dhankuta to standardize the time and method of grafting and to assess the success and growth of mandarin saplings. Scions taken from ‘Khoku Local’ mandarin were grafted onto one-year-old trifoliate orange seedling rootstocks by shoot tip and veneer methods in eight different dates starting from 29th October, 2009 to 12th February, 2010 at 15 days interval. The grafts were planted inside closed tunnel of jute and plastic sheet at 10×10 cm spacing in 50×60 cm2 experimental plots in two factorial split-plot design with three replications per treatment, containing 30 grafts per plot. The grafting methods were allotted on main-plots and the dates on sub-plots randomly. The success and growth of sapling was significantly affected by the dates while the methods had no effect. Study results showed that the highest success (96.11 %) was found on 13th January, followed by 28th January (91.11%) and the least (51.67%) on 29th October grafting. The mortality of sprouted grafts was the lowest (0.17%) in 29th December grafting, while it was observed higher in earlier and late season grafting. Observation on growth taken at 180 days after grafting in successful grafts showed that 29th October had the highest number of primary branches (2.2); 14th November had the highest number of leaves (48.47) and secondary branches (2.505); 29th December gave the maximum sapling height (32.86 cm); 13th January produced the lowest number of leaves (21.93) per sapling and 28th January produced the lowest number of primary (1.533) and secondary branches (1.172) per sapling. From the study it was revealed that in Dhankuta, the most appropriate time of grafting was 2nd to 4th week of January. Nepal Journal of Science and Technology Vol. 14, No. 1 (2013) 23-30 DOI: http://dx.doi.org/10.3126/njst.v14i1.8873